DIRECTIONS FOR THE DEVELOPMENT OF FOREIGN INVESTMENT ATTRACTION INTO THE COUNTRY'S ECONOMY (Conferencea, 2024)
Activation of external and domestic investment flows into sectors of the national economy is one of the critical factors ensuring sustainable economic development. In this context, large-scale attraction of foreign investment is of primary importance for the development of the national economy.